2022
DOI: 10.1111/risa.13943
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated consignment simulation to support risk‐based inspection design

Abstract: Invasive nonnative plant pests can cause extensive environmental and economic damage and are very difficult to eradicate once established. Phytosanitary inspections that aim to prevent biological invasions by limiting movement of nonnative plant pests across borders are a critical component of the biosecurity continuum. Inspections can also provide valuable information about when and where plant pests are crossing national boundaries. However, only a limited portion of the massive volume of goods imported dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…We showed that overdispersion (i.e., the fact that consignments in the same pathway have different infestation rates) is a common feature of border biosecurity data. The few other studies that looked into this issue also found evidence of overdispersion in Japan, the United States, and Australia (Clark et al, 2023;Montgomery et al, 2022;Yamamura & Sugimoto, 1995). We then derived a propagule pressure equation for overdispersed pathways and used it to formulate an optimal sample size under budget constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that overdispersion (i.e., the fact that consignments in the same pathway have different infestation rates) is a common feature of border biosecurity data. The few other studies that looked into this issue also found evidence of overdispersion in Japan, the United States, and Australia (Clark et al, 2023;Montgomery et al, 2022;Yamamura & Sugimoto, 1995). We then derived a propagule pressure equation for overdispersed pathways and used it to formulate an optimal sample size under budget constraints.…”
Section: Discussionmentioning
confidence: 99%
“…While we could simulate the filtering effect of inspections on the different consignments that arrive at the border using Monte Carlo methods (Montgomery et al., 2022), the Bayesian framework provides a more tractable approach to this problem. In this section, we assume that pathways are overdispersed and that the distribution of infestation rate among different consignments of a pathway can be modeled by a beta distribution.…”
Section: Reallocating Sampling Effort Can Reduce Propagule Pressurementioning
confidence: 99%
“…It has been used in collaboration with government and other partners to forecast the spread of Phytophthora ramorum , the causal agent of sudden oak death, and spotted lanternfly (Gaydos et al, 2021; Jones et al, 2021). Together with PoPS Border, a consignment inspection simulator used for designing dynamic, risk‐based sampling protocols at national ports of entry (Montgomery et al, 2023), these three models form a suite of tools developed to support phytosanitary management decisions along the biosecurity continuum.…”
Section: Introductionmentioning
confidence: 99%